Interleukin-6 gene variants are associated with reduced risk of chronicity in hepatitis B virus infection in a Malaysian population - Riazalhosseini, Behnaz; Mohamed, Zahurin; Apalasamy, Yamunah Devi; Shafie, Noor Shafila; Mohamed, Rosmawati (Spandidos Publications, 2018)
Interleukin-6 (IL-6) is a cytokine with a critical role in regulating the immune response to infectious disease. Studies have indicated that polymorphisms in the IL-6 gene may be linked to hepatitis B virus (HBV) infection. The purpose of the present study was to examine the association among IL-6 SNPs and haplotypes with HBV infection risk in a Malaysian population. A total of 1,246 Malaysian subjects with and without chronic hepatitis B were recruited for this study. Three IL-6 polymorphisms (rs2069837, rs1800796 and rs2066992) were genotyped using a Sequenom MassARRAY® platform. The results suggested that GC and CC genotypes of rs1800796 as well as GT and TT genotypes of rs2066992 were associated with protection against HBV infection (P<0.001). Furthermore, haplotypes GG and CT exhibited a significant association with protection against HBV (P=0.003 and =0.005, respectively); and haplotypes GG and CT exhibited a significant association with clearance of HBV infection (P=0.035 and =0.037, respectively). The present study indicates that two IL-6 SNPs (rs1800796 and rs2066992) are associated with clearance of chronic HBV or protection against HBV infection at allelic, genotypic and haplotypic levels.